Models and modelling of dynamic moments of inertia of human body - Dodig, M. (International Journal of Sports Science, 2016)
From the biomechanical standpoint, the dynamic moment of inertia in the kinetic structure plays an important role; especially when it comes to executing movement in open and closed kinetic chains. The main task of the analysis is focused on models and modelling of dynamic moment of inertia of specific body parts as well as the entire body. Some important definitions of dynamic moments of inertia have been pointed out, based on the approximate geometric shapes of specific segments and anthopometric sizes. For each body configuration, solid body parts of simple geometric shapes (circular cylinders, sticks and ellipsoids) were used. The suggested model for the head, neck, and fist was modelled with the help of the ellipsoid; the model for the forearm, upper arm, lower leg, upper leg was modelled with the help of cylinders; and for the torso and foot with the help of the parallelepiped. By knowing the sequential body configuration and the time-shift, it is possible to calculate the dynamic moment of inertia. The suggested models for body, arm, and leg were those in which the potential configurations and the influential proportions of distribution of mass were analysed. The choosing of the optimal models for modelling dynamic moments of inertia was described, and those models were presented as the best approximation of the dynamic moment of inertia in the dynamic sense.